How do the Children from Aquitania, who are Victims of Armed Conflict,live the displacement (2016)
In Colombia, the mobilization of hundreds of displaced people to random places as forced residence is of daily occurrence. Violation of essential principles of human rights and of international humanitarian law is manifested through land abandonment, displacement, anxiety, despair, hunger and an uncertain future that marks entire families under the label of “displaced” affecting mainly the child population. They are groups of farmers from all regions of the country that overnight are forced to migrate to urban area to protect theirlives, without any other option than to start a new life of poverty, with few opportunities and marked by social stigmatization.